Unregistered Early–Age Marriage In The Islamic Law Sociological Perspective (Case Study In Kelua Distric): Unregistered Early–Age Marriage In The Islamic Law Sociological Perspective (Case Study In Kelua Distric) - Ulfah, Aulia; Mukhlisshah, St. (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
The early-age marriage phenomenon has become ordinary for Indonesian society, especially in Kelua District, Tabalong Regency, South Kalimantan Province. Moreover, many of these marriages are carried out privately because they have not yet reached the marriage age according to the Marriage Law provisions. The research problem and purpose this paper is about the dominant factors that influence and the impacts that arise from this unregistered early-age marriage that occur in Kelua District. This paper uses the field research type using a Islamic law sociological approach. Data collection techniques using direct observation and interviews with perpetrators who married early in unregistered and community leaders in Kelua District. The research results show that based on a study of the Islamic law sociological object, the unregistered early-age marriage case that occurred in Kelua District is indeed in accordance with the Islamic law rules. However, there are still many people who do not understand and are not aware of the applicable law that the rules for registering marriages are made based on Islamic law with the benefit principle. Therefore, it is still necessary to continue promote efforts to change people's understanding and behavioral patterns in order to improve overall Islamic family law rules practice.